CFD simulation on enhanced micro-scale heat transfer - Ang, Edwin Ching Jitt (2015)
As electronics and computing technologies continue to advance, the amount of heat flux being generated is also likely to increase. Therefore, better heat dissipation systems will be in demand. With tests on micro-scale heat transfer showing significant heat transfer capabilities, the industry in general is showing more interest in exploring the potential of microchannel systems. However, current microchannels are produced using advanced fabrication methods which are costly. In this project, a technique of achieving micro-scale heat transfer using macro geometries is studied. It involves the use of a cylindrical insert which is placed concentrically in a cylindrical pipe to achieve annular microchannel flow. As the insert can be produced by conventional fabrication techniques, this is a much cheaper method of producing a microchannel that can achieve heat transfer capabilities that are comparable to that of a typical microchannel. Following the preliminary study by Goh et al. [1], this project aims to extend the study by testing a set of seven geometrically varied Inverted Fish Scale (IFS) designs using single-phase water at steady state conditions. Moreover, the Plain insert was tested to establish a benchmark for comparing the heat transfer augmentation in the IFS inserts. The IFS designs can be differentiated by two main parameters - groove pitch (P) and height (e). The channel size (H) is fixed at 300μm for this project. In addition to varying these two ratios, a wide range of flow rates from 2L/min to 8L/min is also used to study the flow effects in different flow regimes. For this study, the heat generation rate is fixed at 1000W. From this, the convection heat transfer coefficient and pressure drop for different inserts can be obtained, and the dimensionless variables such as Nusselt number and Reynolds number can be derived. Using a commercial code in ANSYS Fluent, a three-dimensional conjugate heat transfer model is developed. The results showed that the IFS insert with the largest e/H ratio of 0.7 and moderate P/e ratio of 10 obtained the highest Nusselt number of 67.2 at flow rate of 8L/min, which is an 80% improvement over the Plain insert at the same operating conditions. Nonetheless, similar to the trend identified in Kong [2], the same insert produced significantly larger pressure loss of 425kPa. However, as standard pumps can already handle a maximum differential pressure of up to about 850kPa, this pressure loss is still considered small [3]. Furthermore, by analyzing the distributions of velocity, temperature and turbulence kinetic energy (TKE), the mechanisms that can result in heat transfer enhancement have been identified. They have been found to be related to the boundary layer re-initialization, formation of recirculation region and the early transition to turbulent regime. In general, larger flow rate, larger e/H ratio or smaller P/e ratio produces higher Nusselt number. Besides proving the viability of using macro geometries in micro-scale heat transfer, the results have shown that further enhancements can be achieved with nature-inspired designs. With greater ease in achieving micro-scale effects, this can potentially be used to improve heat exchange designs and have a profound impact on the development of effective heat dissipation technologies in the future.